1998
DOI: 10.1096/fasebj.12.12.1163
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIIIa as a nerve‐associated transglutaminase

Abstract: Recent findings have led to changes in the traditional concept of nerve recovery, including the realization that injured nerves, like any other injured tissue, need the assistance of blood-derived cells and factors in order to heal. We show that factor XIIIa (FXIIIa, the potentially active a2subunit of factor XIII), an enzyme that participates in blood coagulation by stabilizing the fibrin clot, is also active in the nervous system where it may play a key role in the healing of injured tissue. We demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…3) matched well with the period of axon elongation . Furthermore, Monsonego et al (1998) reported that crushed fish optic nerves released FXIII exhibiting TG enzymatic activity. Our retinal explant culture experiments clearly showed that FXIII derived from injured optic nerves induced neurite outgrowth from primed retina with optic nerve injury from 3 days beforehand, but not from unprimed (naïve) retina whose optic nerve was transectioned just before removing the eye in order to make the explants (Fig.…”
Section: Sustained Increase Of Cellular Fxiii Expression In Optic Nermentioning
confidence: 99%
“…3) matched well with the period of axon elongation . Furthermore, Monsonego et al (1998) reported that crushed fish optic nerves released FXIII exhibiting TG enzymatic activity. Our retinal explant culture experiments clearly showed that FXIII derived from injured optic nerves induced neurite outgrowth from primed retina with optic nerve injury from 3 days beforehand, but not from unprimed (naïve) retina whose optic nerve was transectioned just before removing the eye in order to make the explants (Fig.…”
Section: Sustained Increase Of Cellular Fxiii Expression In Optic Nermentioning
confidence: 99%
“…Although the presence of factor XIIIA in these cells has been known for many years, the function of this form is still unclear. Recent reports (13,14,24) suggest that plasma factor XIIIA has specialized functions in certain other tissues and cells independent of its function in the blood. It seems to be associated with peripheral nervous tissue and may play a role in the regeneration of this tissue after injury (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports (13,14,24) suggest that plasma factor XIIIA has specialized functions in certain other tissues and cells independent of its function in the blood. It seems to be associated with peripheral nervous tissue and may play a role in the regeneration of this tissue after injury (24). These authors present circumstantial evidence that XIIIA is at least partially synthesized by macrophages present in the nervous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly expressed in the central nervous system and has functions in neural development, neural regeneration, and others [8, 9]. tTG mediates the posttranslational modification of proteins including the crosslinking and the polypeptide formation.…”
Section: Introductionmentioning
confidence: 99%